The role of education for assessing population health: An analysis of healthy life expectancy by educational attainment for 16 European countries - Markus Sauerberg (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2020)
Healthy life expectancy (HLE) is a prominent summary indicator for evaluating and comparing the levels of population health status across Europe. Variations in HLE, however, do not necessarily reflect underlying differences in health and mortality levels among countries and are particularly sensitive when broken down by population subgroups. For instance, despite European countries showing large HLE inequalities by educational level, these countries are also highly heterogenous regarding their educational population composition, which most likely affects their HLE levels. We demonstrate how this compositional effect shapes HLE levels by providing HLE estimates of educational attainment and gender for 16 European countries using the Sullivan method. We use prevalence data about activities of daily living (ADLs) limitations from the European Union Statistics on Income and Living Conditions (EU-SILC) and mortality data from the Eurostat database. We then quantify the magnitude of educational inequalities based on the composite inequality index (CII). Finally, we express total HLE as the sum of education-specific HLEs, weighted by the educational population structure. As expected, we find large educational inequalities in HLE, with men's CII ranging from about 8.5 years in Portugal to approximately 3 years in Romania. For women, educational inequalities are slightly smaller. The decomposition reveals the population structure's strong effects on HLE, which can elicit misleading conclusions about people's health status and potentially turn HLE into an improper measure of educational differences as opposed to a measure of health gaps. For example, low-, medium-, and highly educated individuals in Portugal show more healthy life years than their counterparts in Poland. Still Poland's total HLE value slightly exceeds that of Portugal, indicating favorable health and mortality conditions in Poland. However, Poland's greater relative number of highly educated individuals in its population is responsible for producing this higher total HLE value. We conclude that education is not only paramount for assessing health inequalities across European countries, but also the population composition by educational attainment, because it drives the differences in HLE levels.
Keywords: 300; Health; mortality; educational inequalities; compositional effects; healthy life expectancy; life expectancy